PRISON AS A REPRODUCTION FIELD OF FEMININITY: A STUDY ON THE WOMEN CONVICTS OF THE OPEN PENAL EXECUTION INSTITUTION IN TURKEY - Seda SALİHOĞLU (Fırat University, 2019)
When the criminological studies on woman are considered, there are generally studies about “victim” women. However, it can be indicated that feminist perspective has not been pursued sufficiently in these studies. In general, we can remark that criminology has been institutionalized to a great extent as a male-dominated field of knowledge. One of the most important issues about female criminality is the prison where women are put to “serve their punishment”. Within feminist approach and based on the sample of Bozkurt Open Penal Execution Institution for Women, the research investigated construction fields of feminine identity types by questioning the relationship between the feminine experience and living conditions in the prison. 32 women convicts were interviewed using in-depth interview. In this way, the aim is to attain knowledge about how women evaluate the living space in the prison and in what degree gender is effective in this evaluation. As the result of the research, it is seen that prisons that cannot quite be “ascribed to” women are generally matched with “masculinity”. The most important indicator of this fact is the existential practices developed by prisoner women within the traditional fabric of gender. Cultural value and economic function of motherhood brings with the home-centred definition of women’s gender. Due to this internalisation, patterns of motherhood as “a source of ordering power” in the minds of the prisoner women determine not only woman’s relationship with society, immediate surrounding and her partner but also give shape to her children’s relationship with her and the father. For some women, “working in an income-generating job” had an inevitable function in the definition of feminine identity. For the majority of the women interviewees the society itself is actually an open prison. Beyond being a field where traditional-moral forms of femininity created in social sphere are also constructed, prisons can sometimes function as shelters for women who suffer under family and social pressure. The reason that prison as a restrictive space provides liberation for some women is that in the prison they do not experience the difficulties caused by gender-based understanding dominant in the outside world like family oppression, violence or being labelled.